2018
DOI: 10.1002/cncr.31889
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance and efficacy of BRAF plus MEK inhibition in patients with melanoma who previously have received programmed cell death protein 1‐based therapy

Abstract: BACKGROUND: Combined BRAF and MEK inhibition (BRAF-MEK) is a standard therapy for patients with BRAF V600-mutant melanoma, but to the authors' knowledge, the tolerance, adverse event (AE) profile, and efficacy have not been well defined in the postprogrammed cell death protein 1 (PD-1) setting. METHODS: Patients with BRAF V600-mutant melanoma who received combined BRAF-MEK after prior PD-1-based therapy were assembled from 4 tertiary care centers in the United States and Australia. Dose modification was define… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 26 publications
3
42
0
Order By: Relevance
“…Such observations have predominately suggested that there may be a detriment to the ORR with immunotherapy (specifically ipilimumab) if it is administered after BRAF inhibition, but the reverse sequence does not influence the ORR with BRAF inhibition . Recently, however, a retrospective series of 78 patients with BRAF V600‐mutant melanoma receiving a BRAF‐MEK combination after PD‐1‐based therapy showed an 83% rate of BRAF‐MEK dose modification, 31% rate of adverse event‐related hospitalization, and median BRAF‐MEK therapy and OS durations of 5.8 and 15.6 months, respectively . Overall, the available retrospective data sets are small, and their findings should be considered on a less urgent level relative to patient‐specific factors and preferences.…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
“…Such observations have predominately suggested that there may be a detriment to the ORR with immunotherapy (specifically ipilimumab) if it is administered after BRAF inhibition, but the reverse sequence does not influence the ORR with BRAF inhibition . Recently, however, a retrospective series of 78 patients with BRAF V600‐mutant melanoma receiving a BRAF‐MEK combination after PD‐1‐based therapy showed an 83% rate of BRAF‐MEK dose modification, 31% rate of adverse event‐related hospitalization, and median BRAF‐MEK therapy and OS durations of 5.8 and 15.6 months, respectively . Overall, the available retrospective data sets are small, and their findings should be considered on a less urgent level relative to patient‐specific factors and preferences.…”
Section: Discussion and Future Directionsmentioning
confidence: 99%
“…However, these observations are based on small case series. Most recently concern has been raised about the tolerability and side effect profile of BRAF/MEK inhibition after anti-PD-1 therapy (19). Indeed, the authors speculated that the increased incidence of treatment interruptions may impact upon the rates of OS.…”
Section: Discussionmentioning
confidence: 99%
“…Anti-PD-1 s also show similar outcomes when used after progression on ipilimumab with or without BRAF inhibitors [27]. Moreover, switching from anti-PD-1 s to BRAF/MEK inhibitors can be associated with significant toxicity problems involving treatment interruption or dose reductions [40]. Thus, switching patients with SD has the potential of causing toxicity issues before such a change in systemic therapy is truly needed.…”
Section: Key Pointsmentioning
confidence: 99%